Oneota flow : the Upper Iowa River and its people - Faldet, David S., 1956- (American land and life series., 2009)
Faldet moves through the history of life along the now-polluted Upper Iowa, always focusing on the ways people depend on the river, the environment, and the resources of the region. He blends contemporary conversations, readings from the historical record, environmental research, and personal experience to show us that the health of the river is best guaranteed by maintaining the biological communities that nurture it. In return, taking care of the Upper Iowa is the best way to take care of our future.